2022
DOI: 10.3390/coatings12050644
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning as a Promising Process to Preserve the Quality and Safety of Meat and Meat Products

Abstract: Fresh and processed meat products are staple foods worldwide. However, these products are considered perishable foods and their deterioration depends partly on the inner and external properties of meat. Beyond conventional meat preservation approaches, electrospinning has emerged as a novel effective alternative to develop active and intelligent packaging. Thus, this review aims to discuss the advantages and shortcomings of electrospinning application for quality and safety preservation of meat and processed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 220 publications
0
15
0
2
Order By: Relevance
“…The addition of natural bioactive molecules into the film matrix may improve the antioxidant properties and its physicochemical and barrier proprieties, hence improving the food preservation properties 22 . Based on the antioxidant property of SOPP evidenced by the present study (Figure 2), the antioxidant potential of gelatin films incorporated with SOPP was assessed and the obtained results are given in Figure 6.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The addition of natural bioactive molecules into the film matrix may improve the antioxidant properties and its physicochemical and barrier proprieties, hence improving the food preservation properties 22 . Based on the antioxidant property of SOPP evidenced by the present study (Figure 2), the antioxidant potential of gelatin films incorporated with SOPP was assessed and the obtained results are given in Figure 6.…”
Section: Resultsmentioning
confidence: 83%
“…However, gelatin‐based films have some drawbacks, including poor water resistance, moisture barrier and low antioxidant/antibacterial properties 20 . To address these shortcomings, gelatin has been combined with other substances like chitosan, soybean polysaccharides and carboxymethyl cellulose to create advanced films with improved characteristics for practical packaging applications 19,21–23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrostatic spinning technique allows the polymer to form nanofibers with a larger specific surface area when preparing nanocomplexes. The ability of natural polymers to load active substances can enable them to release the encapsulated compounds over a certain period of time, which, in practice, can effectively prevent the oxidation of the encapsulated food and avoid contamination by microorganisms [ 56 ]. It has been found that konjac glucomannan is a safe and edible polysaccharide but has some drawbacks in its application as a food active packaging film due to its strong hydrophilicity and lack of mechanical properties and gas barrier.…”
Section: Methods For Preparing Reactive Packaging Materialsmentioning
confidence: 99%
“…Many techniques, such as coacervation, nanoprecipitation, spray-drying, emulsification-solvent evaporation, ionic gelation, and electrochemical-based technologies, for the nanoencapsulation of bioactive compounds are available [ 171 ]. In recent years, several studies have highlighted the efficacy of electrospinning and electrospraying over the considered traditional encapsulation techniques [ 172 , 173 , 174 ]. Furthermore, these techniques are considered convenient due to the absence of heat for the thermal preservation of bioactive substances, and they are able to achieve high encapsulation efficiency values, ensuring the stability of compounds upon processing.…”
Section: Active Pla-based Materialsmentioning
confidence: 99%